GEOLOGICAL AND GEOPHYSICAL SURVEY ON THE METALLOGENIC OF THE MANGANESE MINING SITE OF BOUARFA, HIGH ATLAS, MOROCCO - A., Wafik; A., Najine; Z., Ouzarban; F., Redouani (European Scientific Journal, ESJ, 2015)
The Bouarfa manganese site is located a few kilometers west of Bouarfa city on the "border chain" of North Tamlelt Moroccan High Atlas. Our Geological and geophysical investigations, helped to highlight some structural elements. It also helped to characterize the mineralized levels and point out that Bouarfa manganese is a Mississipy Valley Type (MVT). The manganese oxide beds were observed at the lower part of the banded dolomite. Manganese deposit occurs also as karsts within the massive dolomite. Mineralization is associated to the dolomite bench Middle Lias. Therefore, iron oxide and manganese forms irregular clusters and a more capricious distribution. Generally, the manganese indices are numerous and are scattered over a relatively large area allocated to Lias Medium. Manganese mineralization in the study area is in the following forms: 1. Carbonate mineralization diffuse low, but with anomalous zones of 2 to 3%, which seems to exist in the entire series of the cover to the top of the bar Hamaraouët. 2. A syngenetic manganese oxides beds mineralization with lamination (level benchmark of Hamaraouët) (several kilometers). 3. An alternative mineralization in the Hamaraouët bar, which unlike the previous one, is closely related to tectonics. 4. Epigenetic vein mineralization in the upper conglomerates. Earlier in the mineralized series, it also appears to be linked to fairly significant flaws. 5. Mineralization type "run" in Ain Beida is indeed related to a discontinuity surface that corresponds to a paleosurface emersion.